2006
DOI: 10.2337/db05-1373
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Blunts Insulin-Mediated Microvascular Recruitment in Human Forearm Muscle

Abstract: We have previously shown that skeletal muscle capillaries are rapidly recruited by physiological doses of insulin in both humans and animals. This facilitates glucose and insulin delivery to muscle, thus augmenting glucose uptake. In obese rats, both insulin-mediated microvascular recruitment and glucose uptake are diminished; however, this action of insulin has not been studied in obese humans. Here we used contrast ultrasound to measure microvascular blood volume (MBV) (an index of microvascular recruitment)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
303
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(322 citation statements)
references
References 35 publications
12
303
7
Order By: Relevance
“…This is in contrast to a recent study by Clerk et al (51) that demonstrated insulin significantly increased skeletal muscle capillary volume without changing capillary flow velocity in lean (but not obese) individuals. This discrepancy with our study may be due to technical differences including lower sensitivity and precision of the MVI technique we used compared with the Power imaging technique used by Clerk et al (51) and inclusion of small arteries (diameter Ͻ350 m) in our analysis. The increase in microvascular flow velocity we observed may reflect flow dynamics in small arteries consistent with insulin-enhanced blood flow in the proximal brachial artery.…”
Section: Discussioncontrasting
confidence: 54%
“…This is in contrast to a recent study by Clerk et al (51) that demonstrated insulin significantly increased skeletal muscle capillary volume without changing capillary flow velocity in lean (but not obese) individuals. This discrepancy with our study may be due to technical differences including lower sensitivity and precision of the MVI technique we used compared with the Power imaging technique used by Clerk et al (51) and inclusion of small arteries (diameter Ͻ350 m) in our analysis. The increase in microvascular flow velocity we observed may reflect flow dynamics in small arteries consistent with insulin-enhanced blood flow in the proximal brachial artery.…”
Section: Discussioncontrasting
confidence: 54%
“…3,19 In obese subjects, the insulin-stimulated muscle microvascular recruitment is impaired. 23 We have shown, by directly visualizing capillaries in human skin, that systemic hyperinsulinemia is capable of increasing the number of perfused capillaries. 7,18 This insulin-dependent capillary recruitment is impaired in obese insulin-resistant subjects.…”
Section: Microvascular Dysfunction As a Cause Of Insulin Resistancementioning
confidence: 99%
“…36 Thus, shared insulinsignaling pathways in metabolic and vascular target tissues with complementary functions may provide a mechanism to couple the regulation of glucose with hemodynamic homeostasis. 23 The net hemodynamic action of insulin is dependent on a balance between its vasodilator and vasoconstrictor effects.…”
Section: Impairment Of Insulin-mediated Capillary Recruitment: Possibmentioning
confidence: 99%
“…This can lead to insulinstimulated vasoconstriction or impaired vasodilation if signaling from the insulin receptor to eNOS is inhibited pharmacologically or downregulated by insulin resistance, as seen in conditions of obesity and hypertension in animal studies (9,10). In obese human subjects, a blunted (micro-)vascular responsiveness to insulin has been demonstrated (11)(12)(13). Thus, endothelial insulin resistance may contribute to the development of hypertension in obesity and account in part for the epidemiological relationship between hypertension and insulin resistance (6,8,14).…”
Section: Introductionmentioning
confidence: 99%